“When It’s a Girl, They Have a Chance to Have Sex With Them. When It’s a Boy…They Have Been Known to Rape Them”: Perceptions of United Nations Peacekeeper-Perpetrated Sexual Exploitation and Abuse Against Women/Girls Versus Men/Boys in Haiti - Bartels, Susan A.; King, Carla; Lee, Sabine (Frontiers in Sociology, 2021)
Peacekeeping missions have been marred by reports of sexual exploitation and abuse (SEA) against local community members. However, there is limited research on how SEA against women/girls versus men/boys is perceived in peacekeeping host societies. In 2017 we collected micro-narratives in Haiti and then conducted a thematic analysis to understand how peacekeeper-perpetrated SEA was perceived by local community members comparing SEA against women/girls versus SEA against men/boys. Both male and female participants used language which suggested the normalization, in Haitian society, of both transactional sex with and rape of women/girls by UN personnel. In contrast, peacekeeper-perpetrated SEA against men/boys was viewed as unacceptable and was associated with homosexuality and related stigmatization. Overall, our results suggest that in Haiti, inequitable gender norms, the commodification of female sexuality, and homophobia result in SEA against males being recognized as a wrong that elicits outrage, while SEA against women/girls has been normalized. It is important to address the normalization of SEA against women/girls to prevent future violence and to recognize that SEA is also perpetrated against men/boys. Survivor-centered programs, sensitive to the needs of both male and female survivors, are required.